2011
DOI: 10.1029/2010gl045820
|View full text |Cite
|
Sign up to set email alerts
|

Linking volcanic tremor, degassing, and eruption dynamics via SO2imaging

Abstract: [1] Recently developed UV cameras offer improvement in remote sensing of volcanic SO 2 , with temporal resolutions of ∼1 Hz and synoptic plume views. Integrated UV camera and seismic measurements recorded in January 2009 at Fuego volcano, Guatemala, provide new insight into the system's shallow conduit processes. High temporal resolution SO 2 data reveal patterns of SO 2 emission rate relative to explosions and seismic tremor that indicate tremor and degassing share a common source process. Progressive decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 27 publications
11
115
1
Order By: Relevance
“…These experimental outcomes are as would be expected, given that tremor is anticipated to increase with elevated bubble concentrations in magmas, or the more rapid flow of bubbles in the conduit, scenarios which would both correspond to periods of elevated gas release. In two of the studies, intriguing lag relationships were identified [20,44]. In particular, in Nadeau et al [20], a trend of increasing temporal lags between the seismic and gas flux time series was observed in the period following explosions, implying perhaps that the source of seismic energy was becoming progressively deeper within the conduit due to the rheological stiffening of the magma downwards from the top of the column.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 99%
See 4 more Smart Citations
“…These experimental outcomes are as would be expected, given that tremor is anticipated to increase with elevated bubble concentrations in magmas, or the more rapid flow of bubbles in the conduit, scenarios which would both correspond to periods of elevated gas release. In two of the studies, intriguing lag relationships were identified [20,44]. In particular, in Nadeau et al [20], a trend of increasing temporal lags between the seismic and gas flux time series was observed in the period following explosions, implying perhaps that the source of seismic energy was becoming progressively deeper within the conduit due to the rheological stiffening of the magma downwards from the top of the column.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 99%
“…In two of the studies, intriguing lag relationships were identified [20,44]. In particular, in Nadeau et al [20], a trend of increasing temporal lags between the seismic and gas flux time series was observed in the period following explosions, implying perhaps that the source of seismic energy was becoming progressively deeper within the conduit due to the rheological stiffening of the magma downwards from the top of the column. In Pering et al [44], bursts in CO 2 outgassing were reported (derived from the UV cameras in tandem with Multi-GAS [3] units) which preceded spikes in seismicity, raising intriguing questions regarding the causal processes that might link these phenomena in this case.…”
Section: Combination Of Uv Camera Degassing Data With Geophysical Datmentioning
confidence: 99%
See 3 more Smart Citations